Low maternal pregnancy‐associated plasma protein A during the first trimester of pregnancy and pregnancy outcomes. Issue 1 (3rd November 2016) - Kaijomaa, Marja; Rahkonen, Leena; Ulander, Veli‐Matti; Hämäläinen, Esa; Alfthan, Henrik; Markkanen, Helene; Heinonen, Seppo; Stefanovic, Vedran
Abstract: Objective: To assess the association between pregnancy‐associated placental protein A (PAPP‐A) levels in the first trimester of pregnancy and adverse pregnancy outcomes. Method: A retrospective study included data from a group of patients in the first trimester of pregnancy with PAPP‐A levels below 0.3 multiples of median who attended the Helsinki University Hospital, Finland, between January 1, 2009 and December 31, 2012; an age‐matched control group of patients with PAPP‐A levels 0.9–1.1 multiples of median was also enrolled. The incidences of adverse pregnancy outcomes in the two groups were compared. Results: There were 961 patients included in each of the groups. Significantly increased risks of aneuploidies (odds ratio [OR] 116.0; 95% confidence interval [CI] 16.2–836.6) and spontaneous abortion (OR 7.7; 95% CI 2.7–22.0) were observed among patients with low PAPP‐A (both P <0.001). Preterm delivery (OR 2.5, 95% CI 1.8–3.5), pre‐eclampsia (OR 10.9, 95% CI 4.3–27.6), and small for gestational age neonates (OR 4.9, 95% CI 3.2–7.5) were also observed more frequently among patients with low PAPP‐A (all P <0.001). There were 9 (0.9%) stillbirths recorded among patients with low PAPP‐A and none recorded in the control group. Conclusion: Low PAPP‐A was associated with adverse pregnancy outcomes and aneuploidy. These risks should be considered when planning follow‐up for patients with low PAPP‐A pregnancies. Abstract : Low maternal pregnancy‐associated placental protein A was associated with adverse pregnancy outcomes and could be a beneficial indicator for increased patient follow‐up during pregnancy.